2022
DOI: 10.1186/s12889-022-13351-1
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the complex impact of the Covid-19 pandemic on children with overweight and obesity: a comparative ecological analysis of parents’ perceptions in three countries

Abstract: Background The Covid-19 pandemic has changed children’s eating and physical activity behaviours. These changes have been positive for some households and negative for others, revealing health inequalities that have ramifications for childhood obesity. This study investigates the pandemic’s impact on families of children aged 2–6 years with overweight or obesity. Methods Drawing on interviews conducted as part of a randomised controlled trial (RCT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
1
14
0
5
Order By: Relevance
“…Using Bronfenbrenner's ecological systems theory (EST) ( 82 , 83 ) as a lens enables us to better understand why the pandemic has had considerable impact on children's mental health. According to the EST, a child develops through the interaction of different systems (i.e., the micro-, meso-, exo-, macro- and chronosystems) from the closest to the broadest ( 84 ). During the pandemic, the children's microsystem has been compromised ( 38 , 85 ) by a number of restrictions, such as the prolonged closure of schools, homeschooling and the absence of social support (peer relationships and extended families).…”
Section: Discussionmentioning
confidence: 99%
“…Using Bronfenbrenner's ecological systems theory (EST) ( 82 , 83 ) as a lens enables us to better understand why the pandemic has had considerable impact on children's mental health. According to the EST, a child develops through the interaction of different systems (i.e., the micro-, meso-, exo-, macro- and chronosystems) from the closest to the broadest ( 84 ). During the pandemic, the children's microsystem has been compromised ( 38 , 85 ) by a number of restrictions, such as the prolonged closure of schools, homeschooling and the absence of social support (peer relationships and extended families).…”
Section: Discussionmentioning
confidence: 99%
“…6 Qualitative studies from North America and Europe stated that the restrictions had influenced food and activity habits. 5,21 The pandemic restrictions have affected the physical and mental health of both children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…24 These habits were more negatively affected in families that had less resilience and found it more difficult to adapt. 5,7 This implies that inequalities in health increased during the COVID-19 pandemic. The particular increase in obesity over time, and the reported inequalities in health, implies an urgent need for both general and targeted interventions in healthcare, as well as in the entire society.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the UPF industry is leveraging the COVID - 19 pandemic in the Philippines to counter food and nutrition policy, arguing the need for economic expansion and positioning themselves as a provider of essential food and nutrition services. We argue that the COVID - 19 pandemic instead emphasises the need for food and nutrition policies, to reduce diet - related diseases, many of which are key risk factors for adverse outcomes associated with COVID - 19 [ 55 , 56 ]. We are not the first to report on industry and other coalitions capitalising on such events.…”
Section: Discussionmentioning
confidence: 99%